Procedural Justice: Relationship between HR Development, Motivation, Competence, and Employees Performance - Nuning Nurna Dewi; Riza Bahtiar Sulistyan; Mohammad Reevany Bustami (Image : Jurnal Riset Manajemen, 2025)
The purpose of this study is to test and analyze the important role of procedural justice as a mediator of the influence of human resource development, motivation, and competence on employee performance. The method used in this study is a quantitative method. The sample used was 102 employees in PT. Kasih Jaya Sejahtera, Indonesia. The results of the research show that directly human resource development, motivation, competence, and procedural justice have a significant effect on employee performance. Motivation and competence have a significant effect on procedural justice. Indirectly, motivation and competence have a significant effect on employee performance through procedural justice. The uniqueness of the findings shows that human resource development does not have a significant effect on procedural justice. Human resource development also does not have a significant effect on employee performance through procedural justice. Based on these findings, PT. Kasih Jaya Sejahtera is advised to place more emphasis on the application of procedural justice in management policies and practices to maximize the impact of motivation and competence on employee performance.